Antecedentes do workaholism: análise à luz da autoeficácia e da cultura organizacional - Ramadam, Amanda Oliveira (2024)
Workaholism is understood as excessive and compulsive attitudes towards work, which can be due to a series of factors. This study pays special attention to individual and contextual factors, namely self-efficacy and organizational culture. Self-efficacy refers to the belief in one's ability to perform tasks and achieve goals, while organizational culture encompasses the values and practices shared within an organization. Therefore, this work has the general objective of analyzing the influence of self-efficacy and organizational culture on the perception of workaholism among members of startups in southern Brazil. To this end, descriptive and exploratory research was conducted, through a quantitative study of data collection and analysis. 381 professionals who work in startups in the southern region of Brazil (Paraná, Rio Grande do Sul and Santa Catarina) participated in the survey research, who responded to an online questionnaire composed of the Workaholism Scale, the General Self-Efficacy Scale and by the Brazilian Instrument for Assessment of Organizational Culture, reduced version (IBACO). The data obtained were analyzed with the support of SPSS and AMOS software, using descriptive statistics, Confirmatory Factor Analysis and Structural Equation Modeling. As a result, it was possible to verify that startup professionals have a moderate tendency towards workaholism, high self-efficacy and work in an organizational environment that values employee satisfaction and well-being and promotes collaborative actions. Furthermore, two study hypotheses were confirmed. Hypothesis 1, in the analyzed context, was rejected, indicating that self-efficacy exerts a negative influence on workaholism, and suggesting that professionals with greater confidence in their abilities tend to be less prone to workaholism. Furthermore, it was shown that organizational culture also significantly impacts the perception of workaholism (hypothesis 2). Finally, it was found that organizational culture can strengthen professionals' self-efficacy, influencing their attitudes towards work and their ability to face challenges (hypothesis 3). Such results provide important information for the formulation of organizational policies and practices aimed at preventing and managing workaholism, especially in startup contexts, where organizational culture can play an even more preponderant role in shaping employees' work behavior.